High power lithium-ion hybrid electrochemical capacitors using spinel LiCrTiO4 as insertion electrode - Aravindan, Vanchiappan (2013)
We report the synthesis and electrochemical performance of sub-micron size LiCrTiO4 particles prepared by a solid-state approach. X-ray diffraction and transmission electron microscopic studies are used to analyze the structural and morphological properties, respectively, of the synthesized powders. Electrochemical Li-insertion properties are evaluated in half-cell configurations (Li/LiCrTiO4) by means of both galvanostatic and potentiostatic modes between 1 and 2.5 V vs. Li. Reversible insertion of almost one mole of lithium (155 mA h g−1) is noted at a low current rate of 15 mA g−1 and rendered an excellent cycling profile as well. A non-aqueous Li-ion electrochemical hybrid capacitor (Li-HEC) is fabricated with an optimized mass loading of activated carbon (AC) cathode and synthesized LiCrTiO4 as anode in 1 M LiPF6 in ethylene carbonate–diethyl carbonate solution and cycled between 1 and 3 V under ambient conditions. The Li-HEC delivered maximum specific energy and power densities of 23 W h kg−1 and 4 kW kg−1, respectively.